Transcriptome analysis and systemic RNAi response in the African sweetpotato weevil (Cylas puncticollis, Coleoptera, Brentidae - Prentice, K.; Pertry, I.; Christiaens, O.; Bauters, L.; Bailey, M.; Niblett, C.; Ghislain, M.; Gheysen, G.; Smagghe, G. (Public Library of Science, 2015)
The African sweetpotato weevil (SPW) Cylas puncticollis Boheman is one of the most important constraints of sweetpotato production in Sub-Saharan Africa and yet is largely an uncharacterized insect pest. Here, we report on the transcriptome analysis of SPW generated using an Illumina platform. More than 213 million sequencing reads were obtained and assembled into 89,599 contigs. This assembly was followed by a gene ontology annotation. Subsequently, a transcriptome search showed that the necessary RNAi components relevant to the three major RNAi pathways, were found to be expressed in SPW. To address the functionality of the RNAi mechanism in this species, dsRNA was injected into second instar larvae targeting laccase2, a gene which encodes an enzyme involved in the sclerotization of insect exoskeleton. The body of treated insects showed inhibition of sclerotization, leading eventually to death. Quantitative Real Time PCR (qPCR) confirmed this phenotype to be the result of gene silencing. Together, our results provide valuable sequence data on this important insect pest and demonstrate that a functional RNAi pathway with a strong and systemic effect is present in SPW and can further be explored as a new strategy for controlling this important pest.